The Potential of Neolamarckia cadamba Seedling in Improving Growth Performance and Yield of Zea mays under Different Precipitation Patterns - Romia Rona, Tagang; Hollena, Nori; Walftor, Dumin; Wee, Sze Yee; Ho, Wei Seng; Mohamad Hilmi, Ibrahim (UNIMAS Publisher, 2025)
Climate change is altering rainfall, with more droughts and severe storms that harm agriculture. These shifts in temperature and precipitation disrupt soil moisture, which is essential for the growth of staple crops. Therefore, this study was conducted to investigate the effects of integrating Neolamarckia cadamba with Zea mays on growth performance under different precipitation patterns: low (T1), normal (T2) and high (T3). The experiment was conducted in a completely randomised block design (CRBD), with the first block representing N. cadamba integrated with Z. mays as agroforestry, the second block representing only Z. mays as a crop and the third block only N. cadamba as a tropical tree species. The growth parameters (number of leaves, diameter, plant height and chlorophyll content) were measured 120 days after planting and the yield parameters (fresh weight, dry weight, number of kernels, fresh weight of kernel, dry weight of kernel) were measured after harvesting. The results showed significant effects of rainfall and agroforestry integration on maize yield in term of dry weight, number of kernels, kernels fresh weight and kernel dry weight. Kernel yield parameters, including fresh weight and kernel number, were highest under T2 and T3 in the agroforestry (AGRO), indicating improved availability of resources and soil conditions by N. cadamba. In term of practices, AGRO produced higher chlorophyll (SPAD: 29.44 ± 1.44 vs 22.47 ± 2.31; P < 0.05) and dry weight (277.24 ± 11.68 g vs 216.84 ± 23.47 g; P < 0.05) than NON-AGRO. These results show an ecological trade-off such as in normal and wet conditions N. cadamba cools the canopy and conserves soil moisture, raising Z. mays performance while under drought, root water pre-emption and reduced light increase competition and depress kernel. At farm level, border or alley planting of N. cadamba with Z. mays can be promoted under normal and wet conditions, while wider spacing or soil-water conservation is advisable in dry conditions the policymakers can include maize and N. cadamba designs in agroforestry extension as part of climate-smart agriculture.